Health Belief Model Pencegahan Malaria Pada Ibu Hamil - Lestari, Muji; Amal, Fachry; Mulyana, A. Saputri (Jurusan Kebidanan Poltekkes Kemenkes Mamuju, 2023)
Malaria in pregnant women can infect the fetus. Pregnant women are the most vulnerable population because of the greater risk of contracting malaria. This finding is consistent with the findings obtained by the Eijkman team who found that the immunity level of women who were pregnant for the first time was lower than that of women in the second, third, and so on, thus making the group of women with first pregnancies more susceptible to malaria infection. Malaria cases in pregnant women in 2019, were the highest in Papua Province, which was around 1,769 cases. It is necessary to take preventive measures so that no more pregnant women are affected by malaria. The purpose of this study was to determine the relationship between the components of the Health Belief Model which included perceptions of vulnerability, perceptions of the severity of poor health, perceived barriers to taking action, perceived benefits of behavior change and self-efficacy with malaria prevention measures in pregnant women at the Arso Public Health Center, Keerom Papua Province. This research uses a cross-sectional design. The results of the multiple linear regression test showed that perception of severity had the greatest influence value (0.238). The results of each t-test showed that only perception of severity had a positive effect on preventive action, while perceptions of vulnerability, perceived barriers and self-efficacy had no effect. The results of the simultaneous f-test of the five components of the Health Belief Model have no effect on malaria prevention measures in pregnant women. The perception of severity has a positive effect on malaria prevention measures in pregnant women, while the perceived benefits have a negative effect. The other three components of the Health Belief Model have no effect. Simultaneously, the five components of the Health Belief Model do not affect preventive measures.